Effect of continuous and pulsed therapeutic ultrasound in the appearance of local recurrence of mammary cancer in rats - De Rezende, Laura Ferreira; Da Costa, E.C. Silva; Schenka, N. Guimarães Moraes; Schenka, A. Almeida; Uemura, G. [UNESP] (My University, 2012)
Purpose: Ultrasound (US) therapy is an electrothermotherapeutic modality that uses US energy to provoke physical and chemical alterations. US therapy has been widely used in physical therapy. However, in clinical practice, it is contra-indicated in cancer patients due to the possibility of exacerbating tumor growth. Methods: Sixty-eight female Sprague-Dawley rats bred in UNIFAE vivarium were studied. At 50 days of age, 7,12-dimetylbenz(a)anthracene (7,12-DMBA) was administered to 35 rats by gastric gavage to induce mammary cancer. After 90 days the mammary glands of the rats belonging to the group with mammary cancer induction and stimulated by US were removed. Animals received either continuous or pulsed US. US waves were generated at a frequency of 1 MHz during 10 days, with an intensity dose of 0.5 W in the continuous group, and 0.9 W (duty cycle: 20%) in the pulsed group. Results: Among the rats treated with continuous US, 44.4% developed local recurrence, while among the rats treated with pulsed US, 22.2% had local tumor recurrence (p<0.05). No evidence of distant metastases was shown in any of the rats studied. Conclusion: The use of continuous and pulsed therapeutic US promoted the development of local recurrence of mammary cancer in female Sprague-Dawley rats in the postoperative period. © 2012 Zerbinis Medical Publications.
Keywords: Breast cancer; Breast cancer recurrence; Physical therapy; Therapeutic ultrasound